A radiative transfer model to simulate light scattering in a compact granular medium using a Monte‒Carlo approach: Validation and first applications. Issue 12 (12th December 2013) - Pilorget, C.; Vincendon, M.; Poulet, F.
<x xml:space="preserve">Abstract</x> [1] A new radiative transfer model to simulate light scattering in a compact granular medium using a Monte‒Carlo approach is presented. The physical and compositional properties of the sample can be specified at the grain scale, thus allowing to simulate different kinds of heterogeneties/mixtures within the sample. The radiative transfer is then calculated using a ray tracing approach between the grains, and probabilistic physical parameters such as a single scattering albedo and a phase function at the grain level. The reflectance and the albedo can be computed at different scales and for different geometries: from the grain scale to the sample one. The photometric behavior of the model is validated by comparing the bidirectional reflectance obtained for various media and geometries with the one of semi‒infinite multilayer models, and a few first applications are presented. This model will be used to refine our understanding of visible/NIR remote sensing data of planetary surfaces, as well as future measurements of hyperspectral microscopes which may be able to resolve spatial compositional heterogeneities within a given sample.